Muslim family law in Western courts - Giunchi, Elisa (Abingdon, Oxon, UK : Routledge, 2014)
'This book focuses on how various aspects of Islamic family law as interpreted and applied by judges in Europe, in Australia and North America. Covering a wide number of countries (Britain, France, Spain, Italy, Norway, Switzerland, the US, Canada, Australia), it uses court transcriptions and observations to discuss a number of specific issue, including how the most contentious marriage-related issues - consent and age of spouses, mahr, polygamy, divorce, and kafalah - are adjudicated'--
Includes bibliographical references and index.
Keywords: Domestic relations (Islamic law) -- Western countries; Conflict of laws -- Domestic relations -- Western countries